Mediating Role of Digital Service Adoption in Enhancing Human Resource Management Capacity of SMEs - Nga, Lu Phi; Tam, Phan Thanh (Ital Publication, 2025)
In the context of rapid digital transformation, small and medium enterprises (SMEs) increasingly recognize the necessity of adopting digital services to enhance their human resource management (HRM) capabilities. This study aims to investigate the mediating role of digital service adoption in improving HRM capacity among Vietnamese SMEs. The Resource-Based View draws upon the Technology-Organization-Environment framework; the research examines how leadership support, organizational readiness, policy mechanisms, perceived benefits, and organizational culture influence digital service adoption and HRM development. A mixed-method was employed, combining qualitative interviews with 30 digital transformation experts across five major cities in Vietnam and a quantitative survey of 1,000 SME managers from July 2024 to February 2025. Structural equation modeling was utilized to test 11 proposed hypotheses. The results demonstrate that digital service adoption significantly enhances HRM capacity and mediates the relationships between organizational factors and HRM outcomes. Leadership support is the strongest predictor of digital adoption and HRM capacity, followed by perceived benefits and policy mechanisms. These findings emphasize the importance of strategic leadership, organizational preparedness, supportive policies, and a digital-friendly culture in fostering successful digital transformation in HRM. The novelty contributes a novel integrated model bridging digital transformation and HRM theories and offers practical insights for SME managers seeking to strengthen workforce capabilities in emerging economies.